Sheaf theory and Paschke duality. Issue 2 (28th August 2013) - Roe, John; Siegel, Paul
Abstract: Let X be a locally compact metrizable space. We show that the Paschke dual construction, which associates to a representation of C 0 ( X ) its commutant modulo locally compact operators, can be sheafified. We use this observation to simplify several constructions in analytic K -homology.